Nutritional status of COVID-19 patients in Iceland: A retrospective study - Sandra Dögg Guðnadóttir 1989- (2022)
Increasing evidence indicates an association between nutritional status (including obesity, malnutrition, and vitamin D status) and COVID-19 disease severeness. However, this association has not been assessed in Iceland. The aim of the study was to describe the nutritional status of hospitalized COVID-19 patients in Iceland and assess whether nutritional status is associated with COVID-19 severeness. Methods: The study is a descriptive retrospective study of 273 patients with COVID-19 admitted to Landspitali, University Hospital in Iceland from February 2020 to March 2021. Information was gathered from hospital records. All patients were screened for risk of malnutrition using a validated screening tool. 25(OH)vitD concentration was analyzed (n=266), and insufficient vitamin D status was defined as 25(OH)vitD <50 nmol/L. Body mass index (BMI) was calculated from height and weight (n=237). Obesity was defined as a BMI of ≥30 kg/m2. Logistical regression analysis was used to assess the association between indicators of nutritional status of patients with COVID-19, and outcomes such as length of stay >7 days, ICU admission and mortality. Results: According to the nutritional screening, 201 (74%) patients were at a medium to high risk of malnutrition. Moreover, medium and high risk of malnutrition was associated with increased risk of hospitalization for >7 days compared to those at a low risk of malnutrition, after correcting for age, gender and comorbidities (diabetes, cardiovascular disease, respiratory system disease, and renal disease) (OR: 10.44; 95% CI: 3.79-28.76; p<0.001 and OR: 55.37; 95% CI: 17.35-176.71; p<0.001, respectively). All patients that were admitted to the ICU (n=41) were at a medium (32%) or high (68%) risk of malnutrition, with significant increased prevalence of ICU admissions amongst those at a high risk of malnutrition (p<0.001) compared with those at a medium risk. High risk of malnutrition also seemed to be associated with mortality compared to those at a low risk of ...